A mixed methods study of the impact of consultant overnight working in an English Emergency Department. Issue 5 (9th August 2018) - Penn, Marion L; Monks, Thomas; Pope, Catherine; Clancy, Mike
Abstract : Background: There is a growing expectation that consultant-level doctors should be present within an ED overnight. However, there is a lack of robust evidence substantiating the impact on patient waiting times, safety or the workforce. Objectives: To evaluate the impact of consultant-level doctors overnight working in ED in a large university hospital. Methods: We conducted a controlled interrupted time series analysis to study ED waiting times before and after the introduction of consultant night working. Adverse event reports (AER) were used as a surrogate for patient safety. We conducted interviews with medical and nursing staff to explore attitudes to night work. Results: The reduction seen in average time in department relative to the day, following the introduction of consultant was non-significant (−12 min; 95% CI −28 to 4, p=0.148). Analysis of hourly arrivals and departures indicated that overnight work was inherited from the day. There were three (0.9%) moderate and 0 severe AERs in 1 year. The workforce reported that night working had a negative impact on sleep patterns, performance and well-being and there were mixed views about the benefits of consultant night presence. Additional time off during the day acted as compensation for night work but resulted in reduced contact with ED teams. Conclusions: Our single-site study was unable to demonstrate a clinically important impact of consultant night working on total time patients spend in the department. Our analysis suggests there may be more potential to reduce total time in department during the day, at our study site. Negative impacts on well-being, and likely resistance to consultant night working should not be ignored. Further studies of night working are recommended to substantiate our results.